ARAHAN PEMENUHAN RUANG TERBUKA HIJAU KOTA BANDA ACEH - Cut Hashfi Fadhila; Kukuh Murtilaksono; Khursatul Munibah (Diponegoro University, 2019)
The earthquake that occurred in Banda Aceh on December 26, 2004, followed by the tsunami along the coastline of the Indian Ocean caused a huge number of casualties and infrastructure destruction including green open space. This article presents the change of Banda Aceh green open space before and after the tsunami, the requirement of Banda Aceh green open space based on vast territory and population, and the development direction of Banda Aceh green open space. The applied method was image interpretation, and classification, analysis of green open space requirement was calculated based on vast territory in accordance with Act No. 26/2007, based on population with green open space requirement standard per capita as in PERMENPU No. 5/PRT/M/2008. Green City Development Program (P2KH) concept which was applied to arrange the development direction of Banda Aceh green open space, and integrated with the land use plan in RTRW of Banda Aceh. The result of green open space wide before and after tsunami analysis showed that even before the tsunami, Banda Aceh green open space still far from sufficient as required of spatial planning constitution (13,92 % of the city area). Right after the tsunami, Banda Aceh green open space was reduced to only remaining about 9,31 % of the city area. Five years later (2010) Banda Aceh green open space was increased to 12,83 % of the city area, and by the year of 2015 Banda Aceh has green open space about 37,51 % of the city area. The requirement of Banda Aceh green open space based on the vast territory is 1.227,18 ha public green open space, and 613,59 ha private green open space, based on total population predicted by 2029 is 687,89 ha. The development direction of Banda Aceh green open space is intensification by increasing the quality of existing green open space and extensification by the acquisition of private land for green open space.